A DNA Segregation Module for Synthetic Cells. Issue 13 (15th August 2022) - Tran, Mai P.; Chatterjee, Rakesh; Dreher, Yannik; Fichtler, Julius; Jahnke, Kevin; Hilbert, Lennart; Zaburdaev, Vasily; Göpfrich, Kerstin
Abstract: The bottom‐up construction of an artificial cell requires the realization of synthetic cell division. Significant progress has been made toward reliable compartment division, yet mechanisms to segregate the DNA‐encoded informational content are still in their infancy. Herein, droplets of DNA Y‐motifs are formed by liquid–liquid phase separation. DNA droplet segregation is obtained by cleaving the linking component between two populations of DNA Y‐motifs. In addition to enzymatic cleavage, photolabile sites are introduced for spatio‐temporally controlled DNA segregation in bulk as well as in cell‐sized water‐in‐oil droplets and giant unilamellar lipid vesicles (GUVs). Notably, the segregation process is slower in confinement than in bulk. The ionic strength of the solution and the nucleobase sequences are employed to regulate the segregation dynamics. The experimental results are corroborated in a lattice‐based theoretical model which mimics the interactions between the DNA Y‐motif populations. Altogether, engineered DNA droplets, reconstituted in GUVs, can represent a strategy toward a DNA segregation module within bottom‐up assembled synthetic cells. Abstract : A DNA segregation module for bottom‐up assembled synthetic cells is realized. It is based on DNA droplets that are engineered to segregate upon enzymatic or photocleavage inside giant unilamellar lipid vesicles (GUVs). The segregation kinetics is altered by the confinement, as confirmed by lattice‐based numerical simulations. DNA segregation is further controlled by temperature, ionic strength, and nucleobase sequence.